Micosis Fungoides en placa - Di Martino, Beatriz; Lezcano, Liz; Menárquez Palanca, Javier; Rodriguez Masi, Mirta; Knopfelmacher, Oilda; Bolla de Lezcano, Laura (Dermatología Venezolana, 2017)
Micosis Fungoides en placa